9 Years Follow-up of a Patient with Pituitary Form of Resistance to Thyroid Hormones (PRTH): Comparison of Two Treatment Periods of D-Thyroxine and Triiodothyroacetic Acid (TRIAC) - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2009)
Patients with pituitary resistance to thyroid hormones (PRTH) exhibit features of hyperthyroidism due to normal sensitivity to thyroid hormones in some of the peripheral tissues. There is a lack of information in the literature on the long-term follow-up and treatment of patients with PRTH. Here, we present long-term (9 years) clinical and biochemical follow-up of a patient with PRTH under the treatment of D-T4 initially (for 1.5 years) followed by TRIAC for 5.5 years. An 11.5 year-old girl was evaluated for goiter, palpitations, heat intolerance, sleep disorders, nervousness and frequent stools for 3 years. Her thyroid function tests were consistent with PRTH. Molecular analysis revealed a heterozygous missense mutation of the TR beta gene at codon 243 in exon 7 (R243Q) and a silent mutation at codon 245 in the index patient and the mother who was later also diagnosed to have PRTH. The patient was started on D-T4 treatment since she exhibited clinical symptoms of hyperthyroidism. After 1.5 years, D-T4 treatment was switched to TRIAC which lasted 5.5 years. During the long course of both treatments, thyroid hormones, TSH, heart rate, thyroid size, and markers of peripheral thyroid status (SHBG and alkaline phosphatase) were monitored. It was concluded that compared to D-T4, TRIAC treatment is more effective in suppressing TSH and lowering thyroid hormone levels in PRTH. However, both treatments were unable to reduce thyroid size. The effects of treatment on symptomatology were also modest. Spontaneous improvement in symptoms was observed with age.
Keywords: pituitary resistance to thyroid hormones; D-thyroxine; triiodothyroacetic acid; TRIAC; HYPERTHYROIDISM; THERAPY; RECEPTOR; CHILD; THYROTROPIN; SECRETION; MUTATION; GENE